Meat consumption among different social groups and specific options for reducing it: a literature review of empirical research - Wiesli, Thea Xenia (Frontiers in Sociology, 2025)
The overconsumption of meat, and the connected overproduction of meat, contribute significantly to climate change, deforestation, biodiversity loss, and public health risks. There is a need to reduce global meat consumption. On average, high- and middle-income countries have the highest levels of meat consumption. However, within individual societies, social groups and classes differ in their food habits and ability to engage in sustainable nutritional habits. This literature review provides information on how socio-economic characteristics, social status, norms, and structural context shape meat consumption, and what interventions can effectively reduce specific social groups' meat consumption. Empirical studies published between 2019 and 2024 were researched and screened, adopting the PRISMA approach. The findings highlight critical variations in meat consumption by gender, age, social status, social norms, and context effects. Effective interventions include tailored approaches such as price incentives, normative messaging, and increasing the accessibility of plant-based options. The discussion underscores the importance of policymakers and stakeholders applying targeted and status-sensitive strategies to support sustainable dietary shifts and to address social inequalities.